MBKM: Connected Curriculum of Arabic Departments in Indonesia - Supardi Supardi; Noor Malihah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This research aims to investigate the implementation of the MBKM (Merdeka Belajar Kampus Merdeka, Independent Learning-Independent Campus)’ Model of the connected curriculum in the Arabic Language departments through an online survey. This research is qualitative in nature by inviting responses from 9 heads of Arabic language departments. The results of this survey show that those Arabic Language departments respond to the MBKM ‘connected curriculum’ model positively, among others, by holding seminars, focus group discussions, and any events on the term of MBKM, and curriculum reviews to adopt the MBKM design. It is also found that there are still a few Arabic language departments that have already implemented the MBKM due to the necessary preparation process. This research reveals several designs those nine departments built, for example, the MBKM design with a limited 20 credits outside the department, a full MBKM of 40 credits outside the department, and 60 credits outside the department, while in terms of the implementation, there was a pattern of MBKM outside the department within the same institution and the department at another institution or university. These various designs show that MBKM provides institutions to adjust their curriculum design to meet their needs by considering the rules of MBKM offered by the government.